How asee can benefit society by making students aware of engineering early - W. . Buchanan (Высшее образование в России)
The President of The American Society for Engineering Education (ASEE) presents the main milestones of its 120-year history in this paper. The author reveals the mission of ASEE,shows its role in modern engineering technology education and draws attention to mainsteps, which can make students aware of engineering early. Special attention is made on how students can economically go to college in conditions of increase of the cost of higher education.